Heat sink process and heat sink assembly

By filling the metal paste on the bottom of the AlN-SiC ceramic shirt and electroplating Cu, Ag and graphene/nano-silver layers, combined with the beryllium oxide insulating layer, the problem that existing heat sink materials are difficult to meet the high heat dissipation and high insulation or conductivity at the same time, achieving the effective application of heat sink components in electronic packaging.

CN119569484BActive Publication Date: 2025-04-25HENZHEN PEPPER GRAY TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202510135146.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-07
Publication Date
2025-04-25
Estimated Expiration
2045-02-07

AI Technical Summary

Technical Problem

Existing heat sink materials are difficult to meet the needs of high heat dissipation, high insulation or high conductivity at the same time, especially in high-power electronic equipment and complex electrical environments, where there is a risk of short circuits and electrical failures.

Method used

A heat sink process is adopted to form a composite substrate by punching and filling the AlN-SiC ceramic substrate and filling the metal paste to form a composite substrate, and then electroplating the Cu layer, Ag layer and graphene/nano-silver composite layer are successively on one side, and the heat dissipation insulating layer is coated on the other side to obtain a heat sink component with good heat dissipation and conductivity on one side and an insulated heat dissipation on the other side.

Benefits of technology

The application of heat sink components in the field of electronic packaging is realized, and the simultaneous demand of high-power equipment for high heat dissipation, conductivity or insulation is met, reducing the risk of short circuits and electrical failures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application provides a heat sink process and a heat sink component, comprising the following steps: S1. punching an AlN-SiC ceramic substrate to obtain an AlN-SiC ceramic substrate with blind holes, and filling the blind holes with metal slurry to obtain a composite substrate; S2. in-situ depositing TiAlN layers on both sides of the composite substrate to obtain a composite substrate; S3. coating a photoresist layer on the side of the composite substrate with the blind hole and patterning it, and then electroplating a Cu layer, an Ag layer, and a graphene / nanosilver composite layer in sequence; coating a heat dissipation insulating layer on the side of the composite substrate without the blind hole to obtain an electroplated plate; S4. stripping the photoresist of the electroplated plate to obtain a heat sink component; the heat sink component obtained in the present application is conductive on one side and insulated on the other side, and has the advantages of good heat dissipation performance and good conductive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of heat sinks, and in particular to a heat sink process and a heat sink component. Background Art

[0002] As electronic devices develop towards high power density, integration, and miniaturization, heat dissipation becomes a key factor restricting their performance and reliability. Traditional heat sink materials such as metals (copper, aluminum) and ceramics (aluminum nitride, beryllium oxide) have limitations in certain applications and cannot meet the requirements of high heat dissipation and high insulation at the same time. Therefore, it is particularly important to develop a new type of heat sink component with good heat dissipation and insulation on one side and good heat dissipation and conductivity on the other side.

[0003] In the related art, metal heat sink materials such as copper and aluminum have high electrical conductivity and high thermal conductivity, but do not have insulation properties. However, in high voltage and complex electrical environments, the use of metal heat sinks may cause short circuits and electrical failures.

[0004] Therefore, the development of a new type of heat sink component with good heat dissipation and insulation on one side and good heat dissipation and conductivity on the other side is of great significance for applications in high-power electronic equipment, high-power semiconductor lasers, aerospace equipment, and 5G communication equipment. Summary of the invention

[0005] In view of the defects in the prior art, the present invention proposes a heat sink process and a heat sink assembly to solve the problem of how to simultaneously improve the heat dissipation and conductivity of the heat sink.

[0006] In order to solve the above technical problems, this application provides the following technical solutions.

[0007] In a first aspect, the present application provides a heat sink process, comprising the following steps:

[0008] S1. Punching a hole on an AlN-SiC ceramic substrate to obtain an AlN-SiC ceramic substrate having a blind hole, and filling the blind hole with a metal slurry to obtain a composite substrate;

[0009] S2. TiAlN layers are deposited in situ on both sides of the composite substrate to obtain a composite substrate;

[0010] S3. A photoresist layer is coated on one side of the composite substrate having a blind hole and patterned, and then a Cu layer, an Ag layer, and a graphene / nanosilver composite layer are sequentially electroplated; a heat dissipation insulating layer is coated on one side of the composite substrate having no blind hole to obtain a plated plate;

[0011] S4. Strip the photoresist of the electroplating board to obtain a heat sink assembly.

[0012] Preferably, the step of electroplating the graphene / nanosilver composite layer is: electroplating the silver-graphene plating solution with the silver sample; the current density of the composite electroplating is 0.3-0.5A / dm 2 , temperature is 20-30℃, time is 5-10h, vacuum degree is 1*10 -4 ~1*10 -2 Pa.

[0013] Preferably, the silver-graphene plating solution comprises a mixture of silver nitrate, a complexing agent, graphene, and a graphene dispersant.

[0014] Preferably, the complexing agent includes one or more of thiosulfate, succinimide, and potassium iodide; the graphene dispersant includes one or more of polyvinyl pyrrolidone and sodium dodecyl sulfate.

[0015] Preferably, the step of in-situ depositing the TiAlN layer is: using trimethylaluminum, titanium tetrachloride and ammonia as precursors and utilizing a thermal atomic layer deposition process to prepare a TiAlN layer on the surface of the composite substrate.

[0016] Preferably, the thermal conductivity of the metal paste is greater than the thermal conductivity of AlN—SiC.

[0017] Preferably, the metal slurry is metal W slurry.

[0018] Preferably, the heat dissipation insulating layer is a beryllium oxide layer.

[0019] In a second aspect, the present application provides a heat sink assembly.

[0020] In a third aspect, the present application provides an application of a heat sink assembly in electronic packaging.

[0021] In summary, compared with the prior art, the present invention achieves the following technical effects: in this application, a Cu layer, an Ag layer, and a graphene / nanosilver composite layer are sequentially electroplated on one side of the composite substrate with a blind hole, and a heat dissipation insulating layer is coated on the side of the composite substrate without a blind hole, thereby obtaining a heat sink component with good heat dissipation and conductivity on one side and good heat dissipation and insulation on the other side, which meets the application requirements in the field of electronic packaging. DETAILED DESCRIPTION

[0022] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0023] The present application provides a heat sink process, comprising the following steps:

[0024] S1. Punching a hole on an AlN-SiC ceramic substrate to obtain an AlN-SiC ceramic substrate having a blind hole, and filling the blind hole with a metal slurry to obtain a composite substrate;

[0025] S2. TiAlN layers are deposited in situ on both sides of the composite substrate to obtain a composite substrate;

[0026] S3. A photoresist layer is coated on one side of the composite substrate having a blind hole and patterned, and then a Cu layer, an Ag layer, and a graphene / nanosilver composite layer are sequentially electroplated; a heat dissipation insulating layer is coated on one side of the composite substrate having no blind hole to obtain a plated plate;

[0027] S4. Strip the photoresist off the electroplating board to obtain a heat sink assembly.

[0028] In the present application, steps S1 and S2 obtain a composite substrate, which has the advantage that using AlN-SiC material as the ceramic base layer can not only make up for the defects of easy hydrolysis of AlN and low density of SiC, but also ensure that the ceramic base layer has the advantages of AlN and SiC, such as high thermal conductivity, high insulation, and high hardness. At the same time, since AlN and SiC have similar density and thermal expansion coefficient, the ceramic base layer has high density and good mechanical properties, which provides a mechanical basis for subsequent drilling and filling, and overcomes the defects of reduced mechanical strength and fragmentation of the ceramic substrate caused by drilling and filling W metal; the present application fills the composite AlN-SiC ceramic base layer with W metal. Metal W, on the one hand, metal W has higher thermal conductivity than AlN-SiC ceramic base layer, can form a fast heat dissipation channel, and improve the heat dissipation performance of the ceramic substrate. On the other hand, the TiAlN layer will form an oxide layer with lower thermal conductivity after oxidation. By using the close contact between W and the TiAlN layer, W can inhibit the phase transformation of TiO2, thereby improving the oxidation resistance of the TiAlN layer and avoiding the problem of reduced thermal conductivity of the TiAlN layer due to oxidation. In the present application, a transition layer TiAlN layer is deposited on the composite AlN-SiC ceramic base layer filled with metal W. Due to the thermal expansion between the ceramic substrate and the subsequent metal cladding copper layer, the transition layer TiAlN layer is formed. The expansion coefficient is different, and the TiAlN layer can reduce the interface stress between the ceramic substrate and the subsequent metal-clad copper layer, improve the bonding strength between the ceramic substrate and the subsequent metal-clad copper layer, and finally achieve a balance between the mechanical properties, thermal conductivity and bonding ability of the ceramic substrate with the metal layer; Steps S3 and S4 are performed by treating the two sides of the composite substrate respectively, removing the photoresist, and obtaining a heat sink component with good heat dissipation and conductivity on one side and good heat dissipation and insulation on the other side, wherein the side with good conductivity is electroplated with a Cu layer, an Ag layer, and a graphene / nanosilver composite layer in sequence to improve the conductivity and heat dissipation. The principle is that copper has good conductivity and thermal conductivity. The electrical and thermal conductivity of the heat sink can be significantly improved. The copper layer, as the electroplating bottom layer, can provide a good substrate, and the copper and TiAlN layers have good bonding. At the same time, the Cu layer is also conducive to enhancing the adhesion of the subsequent silver layer. The high conductivity of the silver layer helps to reduce resistance and improve the efficiency and stability of signal transmission. On the basis of ensuring high adhesion and adaptation with the silver layer, graphene / nanosilver, as a protective layer, can improve the electrochemical properties of the composite material and expand its application range by loading nanosilver particles on the graphene surface. It not only has high conductivity, but also can effectively prevent silver oxidation and corrosion, and can directly perform wire bonding.

[0029] It is worth noting that the present application uses graphene / nanosilver as the outermost layer of the metal layer to be electroplated on the composite substrate, which can achieve wire bonding. The reason is that graphene has excellent electrical conductivity and thermal conductivity, and the addition of nanosilver further improves the electrical conductivity and thermal conductivity of the composite material. Nanosilver particles, nanosilver rods, and nanosilver wires can form a network path in the composite matrix, thereby improving the electrical conductivity and thermal conductivity of the material. At the same time, graphene has high mechanical strength, and the addition of nanosilver can further enhance the mechanical properties of the composite material, so that it can better withstand the mechanical stress during the wire bonding process. The graphene / nanosilver composite can form a good connection with a variety of wire bonding materials (such as gold wire, silver alloy wire, etc.), and has good compatibility. The nanosilver layer on its surface can provide good welding performance, ensuring the reliability of wire bonding connection. In the field of electronic packaging, it can be used to fix electronic components and provide electrical connections; furthermore, the graphene / nanosilver composite can be used as a thermal interface material to form an interface with low thermal resistance between the chip and the heat sink, thereby improving the heat dissipation effect.

[0030] In some embodiments, the step of electroplating the graphene / nanosilver composite layer is: electroplating the silver-graphene plating solution with the silver sample; the current density of the composite electroplating is 0.3-0.5A / dm 2 , temperature is 20-30℃, time is 5-10h, vacuum degree is 1*10 -4 ~1*10 -2 Pa.

[0031] Specifically, the operation of step S3 is as follows:

[0032] Substrate pretreatment: Clean the composite substrate to remove dust, grease and other impurities on the surface. For example, soak it in 50-100 g / L sodium hydroxide solution at room temperature for 0.5-2 hours, then rinse it with distilled water, and then soak it in 200-400 g / L nitric acid solution for 10-60 seconds to neutralize the adsorbed alkaline solution and brighten the substrate surface.

[0033] Patterning by coating a photoresist layer cake: uniformly coating a photoresist layer on one side of the pre-treated composite substrate with a blind hole, for example, by using a spin coating method or a spray coating method, to ensure that the thickness of the photoresist layer is uniform; then using a photolithography machine for exposure and development to form a desired pattern, with an exposure time of 10 to 30 seconds and a development time of 1 to 3 minutes.

[0034] Electroplating Cu layer: prepare a plating solution containing copper ions, such as copper sulfate solution, with a concentration of 200-300 g / L and a pH value of 1.5-2.5; the current density is 1-2 A / dm², the temperature is 20-30°C, and the plating time is 10-30 minutes.

[0035] Electroplating Ag layer: prepare a plating solution containing silver ions, usually using silver nitrate solution, the concentration of the plating solution is 30-60g / L, the pH value is 7-12; the current density is 0.3-0.6A / dm², the temperature is 20-30℃, and the plating time is 10-30 minutes.

[0036] Electroplating graphene / nanosilver composite layer: mixing a protective agent and AgNO3 in an aqueous solution at a mass ratio of 1:1 to 4:1, adjusting the pH to 7 to 12, then adding a reducing agent, heating the reaction, the reaction temperature is 80 to 150°C, the reaction time is 20 to 60 minutes, and the stirring speed is 400 to 800 r / min to obtain a nanosilver plating solution, wherein the protective agent includes one or more of polyvinyl pyrrolidone, polyethylene glycol, and sodium naphthalene formaldehyde sulfonate; the reducing agent includes NaBH4, sodium citrate, polyethylene imine, ethylene glycol, propylene glycol One or more of the following: adding AgNO3, a ligand, graphene, and a graphene dispersant into distilled water, stirring at 800 to 1500 r / min for 1 to 2 hours at room temperature, and then ultrasonically dispersing for 10 to 20 minutes after stirring evenly, wherein the silver-graphene plating solution comprises 30 to 60 g / L of AgNO3, 300 to 600 g / L of a ligand, 20 to 90 g / L of graphene, and 2 to 18 g / L of a graphene dispersant to obtain a silver-graphene plating solution; placing the nanosilver plating solution into a vacuum chamber, wherein the vacuum degree of the vacuum chamber is 1×10 -4 Pa~1×10 -2 Pa, magnetron sputtering coating was adopted, magnetron sputtering was performed for 3 to 30 minutes, and then the pre-silvered sample was placed in the silver-graphene plating solution for silver-graphene vacuum composite electroplating. During the composite electroplating process, the silver-graphene plating solution was continuously stirred, the speed was 500 to 1000 r / min, the current density was 0.3 to 0.6 A / dm², the temperature was 20-30 °C, the electroplating time was 1 to 2 hours, and the vacuum degree was 1×10 -4 Pa~1×10 -2 Pa;

[0037] Post-treatment: After electroplating is completed, the coating is cleaned with deionized water to remove the residual electroplating solution on the surface, and the coating is dried naturally at room temperature or in an oven at 60-80°C for 10-30 minutes.

[0038] In some embodiments, the silver-graphene plating solution includes a mixture of silver nitrate, a complexing agent, graphene, and a graphene dispersant.

[0039] In some embodiments, the ligand includes one or more of thiosulfate, succinimide, and potassium iodide; the graphene dispersant includes one or more of polyvinyl pyrrolidone and sodium dodecyl sulfate.

[0040] In this embodiment, the functions of the complexing agent include controlling the size and distribution of nanosilver particles, preventing agglomeration of nanosilver particles, improving the dispersibility of nanosilver particles, promoting the reduction of silver ions, and improving the electrical conductivity and thermal conductivity of the composite material; the graphene dispersant of the present application is conducive to the uniform dispersion of graphene and nanosilver, and improves the electrical conductivity and thermal conductivity.

[0041] In some embodiments, the step of in-situ depositing the TiAlN layer is: using trimethylaluminum, titanium tetrachloride, and ammonia as precursors, and utilizing a thermal atomic layer deposition process to prepare a TiAlN layer on the surface of the composite substrate.

[0042] In this embodiment, the specific steps of in-situ deposition of TiAlN coating are: heating the composite substrate to 100°C, and adsorbing titanium tetrachloride onto the surface of the composite substrate under a pressure of 50Pa, then adding trimethylaluminum, fumigating for 60s, then flushing away excess TMA with inert gas, and then dripping ammonia water to react to form a TiAlN layer. The above steps constitute an in-situ deposition cycle, and repeating these steps can gradually increase the thickness of the film.

[0043] In some embodiments, the thermal conductivity of the metal paste is greater than the thermal conductivity of AlN-SiC.

[0044] In some embodiments, the metal paste is a metal W paste.

[0045] In this embodiment, the thermal conductivity of metal W is generally 170-180 W / (m·K), and the thermal conductivity of AlN-SiC of the present application is less than the thermal conductivity of metal W, so that the formation of a heat dissipation channel can be achieved. If the thermal conductivity of AlN-SiC is equivalent to or smaller than that of the metallized material W, the heat flux density distribution is relatively uniform, it is not easy to form a heat dissipation channel, and the effect of improving the heat dissipation performance is not obvious.

[0046] In the present application, the preparation method of AlN-SiC material is as follows: silicon powder, carbon black and aluminum nitride are put into a ball mill for ball milling, the balls are separated by a sieve to obtain a uniformly mixed powder, and then the mixed powder is put into a graphite crucible for vacuum sintering to obtain AlN-SiC material.

[0047] In some embodiments, the blind holes are distributed in an array, the diameter of the blind holes is 0.15-0.2 mm, the spacing between adjacent blind holes is 0.4-0.8 mm, the size of the ceramic substrate for the heat sink is (8-10) mm*(8-10) mm, the thickness of the ceramic substrate for the heat sink is 0.8-1.0 mm, and the depth of the blind holes is 0.5-0.7 mm. In this embodiment, the blind holes are arranged in an array distribution as defined in the present application, which can achieve a balance between heat dissipation and mechanical properties. If the pores are too dense, the mechanical properties are poor, and if the pores are too loose, the heat dissipation performance is poor.

[0048] In some embodiments, the heat dissipation insulating layer is a beryllium oxide layer.

[0049] In this embodiment, beryllium oxide, as a heat dissipation insulation layer material, has many advantages such as high thermal conductivity, high insulation, high melting point, good chemical stability, low dielectric constant, low dielectric loss, good mechanical properties and low thermal expansion rate. These characteristics enable the heat sink component to have good heat dissipation insulation in harsh environments such as high power, high temperature, and high frequency. At the same time, the TiAlN coating itself has a certain thermal conductivity, but its thermal conductivity is relatively low. When beryllium oxide is coated on the TiAlN layer, the thermal conductivity of the overall structure can be significantly improved. The high thermal conductivity of beryllium oxide (310W / (m·K)) can effectively conduct the heat generated by the TiAlN layer, thereby improving the heat dissipation efficiency.

[0050] The present application provides a heat sink assembly.

[0051] The present application provides an application of a heat sink assembly in electronic packaging, including but not limited to application in semiconductor laser packaging. In the above scenario, the heat sink assembly is required to be conductive on one side to ensure normal current transmission, and insulated on the other side to prevent electrical short circuit and leakage.

[0052] The present application is further described below by way of specific embodiments.

[0053] Example 1

[0054] A heat sink process comprises the following steps:

[0055] S1. 100g of AlN-SiC powder, 5g of yttrium oxide, and 200ml of n-butanol were mixed and ball-milled, and then 3g of polyvinyl alcohol was added to obtain a slurry. The front blade height of the casting machine was set to 2.0mm, the rear blade height was set to 1.5mm, and the casting speed was set to 0.20m / min. The defoamed slurry was poured into the casting machine and dried on the film belt for 2 hours. A 0.75mm thick blank was obtained. The blank was placed in a graphite hot pressing sintering furnace and sintered under positive pressure in a flowing nitrogen atmosphere. The N2 gas pressure was set at 20KPa, the sintering temperature was 1600℃, and the holding time was 5 hours to obtain an AlN-SiC ceramic substrate; a laser punching process was used to punch holes on the AlN-SiC ceramic substrate to obtain an AlN-SiC ceramic substrate with blind holes, wherein the blind holes were distributed in an array, the diameter of the blind holes was 0.2mm, and the distance between adjacent blind holes was 1.5mm. The distance between the AlN-SiC ceramic substrate and the AlN-SiC ceramic substrate is 0.4mm, the size of the AlN-SiC ceramic substrate is 8mm*8mm, the thickness of the AlN-SiC ceramic substrate is 1.0mm, and the depth of the blind hole is 0.7mm. Then, the AlN-SiC ceramic substrate with the blind hole is immersed in 200ml phosphoric acid, soaked for 1h and taken out; molten metal W slurry is injected into the blind hole, and polished after sintering at 1500℃, and the sintering-polishing steps are repeated 3 times to obtain a composite substrate; the composite substrate is heated to 100℃, and 1g of titanium tetrachloride is adsorbed onto the surface of the composite substrate under a pressure of 50Pa, and then 2g of trimethylaluminum is added, and after fumigation for 60s, the excess TMA is flushed with an inert gas, and then 5ml of ammonia water is dripped into it for reaction to form a TiAlN layer with a thickness of 50nm, and the above steps are repeated 6 times, and the thickness of the TiAlN layer is 300nm, and the composite substrate is obtained;

[0056] S3. Clean the composite substrate to remove dust, grease and other impurities on the surface, for example, soak it in 50g / L sodium hydroxide solution at room temperature for 0.5 hours, then rinse it with distilled water, and then soak it in 200g / L nitric acid solution for 10 seconds to neutralize the adsorbed alkaline solution and brighten the substrate surface; then evenly coat the photoresist layer on the side of the pre-treated composite substrate with blind holes, for example, by spin coating or spray coating to ensure that the thickness of the photoresist layer is uniform; then use a photolithography machine to expose and develop to form the required pattern, with an exposure time of 10 seconds and a development time of 1 minute; prepare a copper ion-containing electroplating solution, such as a copper sulfate solution, with a concentration of 200g / L and a pH value of 1.5; the current density is 1A / dm², the temperature is 20°C, and the electroplating time is 10 minutes; then prepare a silver ion-containing electroplating solution, usually a silver nitrate solution, The concentration of the electroplating solution is 30 g / L, the pH value is 7, the current density is 0.3 A / dm², the temperature is 20°C, and the electroplating time is 10 minutes; then, polyethylene glycol and AgNO3 are mixed in an aqueous solution at a mass ratio of 1:1, the pH is adjusted to 7, and then sodium citrate is added, heated to react, the reaction temperature is 80°C, the reaction time is 20 minutes, and the stirring speed is 400 r / min to obtain a nanosilver plating solution; AgNO3, a ligand, graphene, and a graphene dispersant are added to distilled water, stirred at 800 r / min for 1 hour at room temperature, and ultrasonically dispersed for 10 minutes after stirring evenly. The silver-graphene plating solution includes 30 g / L AgNO3, 300 g / L ligand, 90 g / L graphene, and 18 g / L graphene dispersant to obtain a silver-graphene plating solution, and the nanosilver plating solution is placed in a vacuum chamber, and the vacuum degree of the vacuum chamber is 1×10 -4 Pa, magnetron sputtering coating was adopted, magnetron sputtering was performed for 10 minutes, and then the pre-silvered sample was placed in the silver-graphene plating solution for silver-graphene vacuum composite electroplating. The silver-graphene plating solution was continuously stirred during the composite electroplating process, the speed was 500r / min, the current density was 0.3A / dm², the temperature was 20℃, the electroplating time was 1 hour, and the vacuum degree was 1×10 -4 Pa; after the electroplating is completed, the plated layer is cleaned with deionized water to remove the residual electroplating solution on the surface, and the plated layer is dried naturally at room temperature or in an oven at 80°C for 10 minutes; then a beryllium oxide layer is coated on the side of the composite substrate where no blind hole is provided to obtain an electroplated plate;

[0057] S4. The photoresist of the electroplating board is stripped off by soaking in acetone to obtain a heat sink assembly.

[0058] Example 2

[0059] A heat sink process comprises the following steps:

[0060] S1. 80g of AlN-SiC powder, 5g of yttrium oxide, and 200ml of n-butanol were mixed and ball-milled, and then 3g of polyvinyl alcohol was added to obtain a slurry. The front blade height of the casting machine was set to 2.0mm, the rear blade height was set to 1.5mm, and the casting speed was set to 0.20m / min. The defoamed slurry was poured in and dried on the film belt of the casting machine at a variable temperature for 2 hours to obtain a 0.75mm thick blank. The blank was placed in a graphite hot pressing sintering furnace and sintered under positive pressure in a flowing nitrogen atmosphere. The N2 gas pressure was set at 20KPa, the sintering temperature was 1600℃, and the insulation time was 5 hours to obtain an AlN-SiC ceramic substrate. The AlN-SiC ceramic substrate was punched using a laser drilling process to obtain an AlN-SiC ceramic substrate with blind holes, wherein the blind holes were distributed in an array, the diameter of the blind holes was 0.2mm, and the spacing between adjacent blind holes was 1.5mm. The size of the AlN-SiC ceramic substrate is 0.4 mm, the size of the AlN-SiC ceramic substrate is 8 mm*8 mm, the thickness of the AlN-SiC ceramic substrate is 1.0 mm, and the depth of the blind hole is 0.7 mm. Then, the AlN-SiC ceramic substrate with the blind hole is immersed in 200 ml of phosphoric acid, soaked for 1 hour and taken out; molten metal W slurry is injected into the blind hole, and polished after sintering at 1500° C., and the sintering-polishing steps are repeated 3 times to obtain a composite substrate; the composite substrate is heated to 100° C., and at a pressure of 50 Pa, 1 g of titanium tetrachloride is adsorbed onto the surface of the composite substrate, and then 2 g of trimethylaluminum is added, fumigated for 60 seconds, and then the excess TMA is flushed with an inert gas, and then 5 ml of ammonia water is dripped into it for reaction to form a TiAlN layer with a thickness of 50 nm, and the above steps are repeated 6 times, and the thickness of the TiAlN layer is 300 nm, and the composite substrate is obtained;

[0061] S3. Clean the composite substrate to remove dust, grease and other impurities on the surface, for example, soak it in 50g / L sodium hydroxide solution at room temperature for 0.5 hours, then rinse it with distilled water, and then soak it in 200g / L nitric acid solution for 10 seconds to neutralize the adsorbed alkaline solution and brighten the substrate surface; then evenly coat the photoresist layer on the side of the pre-treated composite substrate with blind holes, for example, by spin coating or spray coating to ensure that the thickness of the photoresist layer is uniform; then use a photolithography machine for exposure and development to form the required pattern, with an exposure time of 10 seconds and a development time of 1 minute; prepare a copper ion-containing electroplating solution, such as a copper sulfate solution, with a concentration of 100g / L and a pH value of 1.5; the current density is 2A / dm², the temperature is 20°C, and the electroplating time is 10 minutes; then prepare a silver ion-containing electroplating solution, usually a silver nitrate solution, and electroplate it. The concentration of the solution is 30g / L, the pH value is 7, the current density is 0.5A / dm², the temperature is 30℃, and the electroplating time is 10 minutes; then, polyethylene glycol and AgNO3 are mixed in an aqueous solution at a mass ratio of 1:2, the pH is adjusted to 7, and then sodium citrate is added, heated to react, the reaction temperature is 80℃, the reaction time is 20 minutes, and the stirring speed is 400r / min to obtain a nanosilver plating solution; AgNO3, a ligand, graphene, and a graphene dispersant are added to distilled water, stirred at 900r / min for 1.5 hours at room temperature, and ultrasonically dispersed for 10 minutes after stirring evenly. The silver-graphene plating solution includes AgNO350g / L, a ligand 100g / L, graphene 70g / L, and a graphene dispersant 20g / L to obtain a silver-graphene plating solution, and the nanosilver plating solution is placed in a vacuum chamber, and the vacuum degree of the vacuum chamber is 1.2×10 -4 Pa, magnetron sputtering coating was adopted, magnetron sputtering was performed for 30 minutes, and then the pre-silvered sample was placed in the silver-graphene plating solution for silver-graphene vacuum composite electroplating. The silver-graphene plating solution was continuously stirred during the composite electroplating process, the speed was 600r / min, the current density was 0.4A / dm², the temperature was 20℃, the electroplating time was 1 hour, and the vacuum degree was 1×10 -4 Pa; after the electroplating is completed, the plated layer is cleaned with deionized water to remove the residual electroplating solution on the surface, and the plated layer is dried naturally at room temperature or in an oven at 60°C for 30 minutes; then a beryllium oxide layer is coated on the side of the composite substrate where no blind hole is provided to obtain an electroplated plate;

[0062] S4. The photoresist of the electroplating board is stripped off by soaking in acetone to obtain a heat sink assembly.

[0063] Example 3

[0064] A heat sink process, other contents are the same as those of Example 1, except that the metal W slurry is replaced by Cu.

[0065] Comparative Example 1

[0066] A heat sink process, the other contents are the same as those of Example 1, except that step S2 is not included.

[0067] Comparative Example 2

[0068] A heat sink process, other contents are the same as those of Example 1, except that in step S3, no electroplating Cu layer is included.

[0069] Comparative Example 3

[0070] A heat sink process, other contents are the same as those of Example 1, except that in step S3, electroplating of an Ag layer is not included.

[0071] Comparative Example 4

[0072] A heat sink process, other contents are the same as those of Example 1, except that in step S3, electroplating of graphene / nanosilver layer is not included.

[0073] Comparative Example 5

[0074] A heat sink process, the other contents are the same as those of Example 1, except that in step S3, the graphene / nanosilver layer is replaced by an Au layer.

[0075] Comparative Example 6

[0076] A heat sink process, other contents are the same as those of embodiment 1, except that a beryllium oxide layer is not included.

[0077] Test and Evaluation

[0078] The heat dissipation performance, conductive / insulating performance and mechanical properties of two different surfaces of the heat sink assembly obtained in each embodiment and comparative example were tested, wherein the side with the blind hole was called side A, and the side without the blind hole was called side B. The heat dissipation performance was evaluated according to GB / T10294-2008 testing thermal resistance, and the lower the thermal resistance, the higher the heat dissipation performance; the mechanical property was tested according to GB / T 4740-2024 to test the strength of the heat sink assembly, and the conductive / insulating performance was tested according to GB / T 3048.2-1994 for electrical conductivity, and the higher the electrical conductivity, the better the electrical conductivity; the results are shown in Table 1.

[0079] Table 1 Test results

[0080]

[0081] In the present application, a Cu layer, an Ag layer, and a graphene / nanosilver composite layer are sequentially electroplated on one side of a composite substrate provided with a blind hole, and a heat dissipation insulating layer is coated on the side of the composite substrate without a blind hole, thereby obtaining a heat sink component with good heat dissipation and conductivity on one side and good heat dissipation and insulation on the other side, thereby meeting the application requirements in the field of electronic packaging.

[0082] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A heat sink process, characterized in that: The following steps are involved: S1. Punching a hole on an AlN-SiC ceramic substrate to obtain an AlN-SiC ceramic substrate having a blind hole, and filling the blind hole with a metal slurry to obtain a composite substrate; the thermal conductivity of the metal slurry is greater than the thermal conductivity of the AlN-SiC ceramic substrate; S2. TiAlN layers are deposited in situ on both sides of the composite substrate to obtain a composite substrate; S3. A photoresist layer is coated on one side of the composite substrate having a blind hole and patterned, and then a Cu layer, an Ag layer, and a graphene / nanosilver composite layer are sequentially electroplated; a heat dissipation insulating layer is coated on one side of the composite substrate having no blind hole to obtain a plated plate; S4. Stripping the photoresist of the electroplating plate to obtain a heat sink assembly.

2. The heat sink process according to claim 1, characterized in that: The steps of electroplating the graphene / nanosilver composite layer are as follows: mixing a protective agent and AgNO3 in an aqueous solution at a mass ratio of 1:1 to 4:1, adjusting the pH to 7 to 12, then adding a reducing agent, heating for reaction, the reaction temperature is 80 to 150°C, the reaction time is 20 to 60 minutes, and the stirring speed is 400 to 800 r / min to obtain a nanosilver plating solution, wherein the protective agent includes one or more of polyvinyl pyrrolidone, polyethylene glycol, and sodium naphthalene formaldehyde sulfonate; the reducing agent includes one or more of NaBH4, sodium citrate, polyethyleneimine, ethylene glycol, and propylene glycol; AgNO3, a ligand, graphene, and a graphene dispersant are added to distilled water, stirred at 800 to 1500 r / min for 1 to 2 hours at room temperature, and ultrasonically dispersed for 10 to 20 minutes after stirring evenly; the silver-graphene plating solution includes AgNO3 30-60 g / L, 300-600 g / L of complexing agent, 20-90 g / L of graphene, and 2-18 g / L of graphene dispersant to obtain a silver-graphene plating solution; the nanosilver plating solution is placed in a vacuum chamber, and the vacuum degree of the vacuum chamber is 1×10 -4 Pa~1×10 -2 Pa, magnetron sputtering coating was adopted, magnetron sputtering was performed for 3 to 30 minutes, and then the pre-silvered sample was placed in the silver-graphene plating solution for silver-graphene vacuum composite electroplating. During the composite electroplating process, the silver-graphene plating solution was continuously stirred, the speed was 500 to 1000 r / min, the current density was 0.3 to 0.6 A / dm², the temperature was 20-30 °C, the electroplating time was 1 to 2 hours, and the vacuum degree was 1×10 -4 Pa~1×10 -2 Pa.

3. The heat sink process according to claim 2, characterized in that: The ligand includes one or more of thiosulfate, succinimide, and potassium iodide; the graphene dispersant includes one or two of polyvinyl pyrrolidone and sodium dodecyl sulfate.

4. The heat sink process according to claim 1, characterized in that: The steps of in-situ deposition of the TiAlN layer are: using trimethylaluminum, titanium tetrachloride and ammonia as precursors and utilizing a thermal atomic layer deposition process to prepare the TiAlN layer on the surface of the composite substrate.

5. The heat sink process according to claim 1, characterized in that: The metal slurry is metal W slurry.

6. The heat sink process according to claim 1, characterized in that: The heat dissipation insulating layer is a beryllium oxide layer.

7. A heat sink component obtained by the heat sink process according to any one of claims 1 to 6.

8. Use of the heat sink assembly according to claim 7 in electronic packaging.

Citation Information

Patent Citations

  • Preparation method of ceramic substrate for high-power LED packaging

    CN102432346A

  • Manufacturing method of efficient cooling ceramic substrate for LEDs

    CN104086223A

Cited By

  • Ultraviolet disinfection equipment for sewage treatment

    CN121181083A

  • An ultraviolet disinfection apparatus for sewage treatment

    CN121181083B